Performance-constrained analogue layout retargeting and optimisation with geometric programming - Wang, Shaoxi; Fan, Xiaoya; Zhang, Shengbing (International journal of electronics, 2014)
Layout parasitic has crucial influence on the performance of analogue integrated circuits. The paper presents a performance-constrained analogue layout retargeting and optimisation scheme. Geometric programming (GP), is a kind of nonlinear optimisation problem, is used in the method, which can be transferred or fitted into a convex optimisation problem based on mathematical analyses. Then, a global optimum solution can be achieved. To achieve the desired circuit performance, performance sensitivities based on layout parasitic are carried out in the analogue layout optimisation. In addition, a central difference method is applied to control parasitic-related layout geometries by constructing a set of performance constraints subject to maximum performance deviation. At last, a two-stage Miller-compensated operational amplifier and a single-ended folded cascode operational amplifier are simulated with the proposed scheme. The automatically generated target layouts can satisfy performance constraints to ensure the desired specifications. The experimental results show that the scheme can achieve effective retargeting of analogue circuit with less layout area and better circuit performance.